Penilaian Kondisi Kesehatan Ekosistem Mangrove di Ayau dan Ayau Kepulauan, Kabupaten Raja Ampat - Rudhi Pribadi; IW Eka Dharmawan; Aditya Sukma Bahari (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2020)
Despite their rather universal distribution in tropical inter-tidal coastal area, mangrove has been identified driven by some physical, chemical and biological factors which might vary one to another site. Muddy waters, sufficient freshwater supply, high tidal inundation were few factors that commonly correlated with an ideal mangrove growth. Ayau Islands, a group of several small islands in the Raja Ampat Islands regency West Papua, however, could be an example of how mangrove was closely interconnected to another tropical coastal ecosystem. The purpose of the study has assessed the health of mangrove ecosystems in Ayau and Ayau Islands. A purposive sampling method was applied for this study, two stations were designated in Kanober Island and one station in Dorekar Island. Three replication sampling plots of 10m x 10m has lied on each station and data were collected following a mangrove monitoring manual.  The result showed at least eight major species, two minor species and 23 association of mangrove components were found in the study site. In general the vegetation in a good condition with a high canopy cover.